Diplurans of subsurface terrestrial habitats in the Iberian Peninsula, with a new species description (Diplura: Campodeidae) - Sendra, Alberto; Jiménez-Valverde, Alberto; Gilgado, José D.; Ledesma, Enrique; Pérez-Suárez, Gonzalo; Cuesta, Eva; Herrero-Borgoñón, Juan J.; Jordana, Rafael; Tinaut, Alberto; Barranco, Pablo; Ortuño, Vicente M. (Zootaxa, 2017)
Although Iberian subsurface terrestrial habitats have been sampled for a half century, they remain poorly known. During the last five years much more sampling of these subsurface habitats has been made, mainly in scree slopes (also called colluvial Mesovoid Shallow Substratum habitats, MSS) but also in alluvial debris of temporal watercourses (alluvial MSS). In our study, diplurans, a basal hexapod group, were extracted from two hundred traps installed in 69 locations in the mountain ranges of six different regions of the Iberian Peninsula, from north to south: Cantabrian, Pyrenees, Iberic System, Central System, Prebaetic and Penibaetic Mountains. A total of 1251 specimens in fifteen dipluran species: thirteen described Campodeidae, one described Japygidae and one new Campodea species inhabiting the alluvial MSS habitats of the watercourses of Prebaetic Mountains. A few populations of these dipluran species show troglobiomorphic features as a consequence of the medium-sized voids of the MSS habitats, such as Campodea grassii Silvestri, 1912, collected in a scree slope connected with a deep subterranean system in Penyas Roset, Prebaetic Mountains. Most species found in MSS habitats are endogean or epiedaphic species living in the area, but this is not the case in Sierra de Guadarrama, where three species (Campodea propinqua Silvestri, 1932, Campodea neusae Sendra & Moreno, 2006 and Campodea zuluetai Silvestri, 1932) unknown in the soil of these mountains have appeared in these subsurface terrestrial habitats.